2016
DOI: 10.1186/s13256-016-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Osseous choristoma of the tongue: two case reports

Abstract: BackgroundOsseous choristoma is a very rare, benign lesion in the maxillofacial region. It appears as a benign mass of normally matured bony tissue covered by the normal epithelium of the tongue. It is usually seen in front of the foramen cecum of the tongue. Surgical excision is the treatment of choice with an excellent prognosis and there have been very few cases of recurrence.Case presentationHere we present two cases of osseous choristoma on the dorsum of the tongue. Case 1 was a 15-year-old Japanese girl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
0
14
0
5
Order By: Relevance
“…e treatment of lingual osseous choristoma is surgical excision. Although recurrence of osseous choristomas of the masseter muscle has been reported [20], there have not been reports on the malignant evolution of lingual osseous choristomas thus far [7]. To our knowledge, our patient is the first reported case of a lingual osseous choristoma that was incidentally removed and cured without surgical interventions.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…e treatment of lingual osseous choristoma is surgical excision. Although recurrence of osseous choristomas of the masseter muscle has been reported [20], there have not been reports on the malignant evolution of lingual osseous choristomas thus far [7]. To our knowledge, our patient is the first reported case of a lingual osseous choristoma that was incidentally removed and cured without surgical interventions.…”
Section: Discussionmentioning
confidence: 65%
“…Less than 100 cases of osseous choristomas of the oral and maxillofacial region have been reported in the English language literature, and the most common site is the tongue, especially the dorsal posterior third of the tongue near the foramen caecum and circumvallate papillae [5]. Gorini et al provided a comprehensive review of 67 cases of the lingual osseous choristomas [6], and eight additional cases of osseous choristoma of the tongue were reported since their review [5,[7][8][9][10][11][12]. Including newly reported cases and our case, the patients' age ranged from five to eighty-nine years (mean: 28.9), with majority of the patients being in the second or third decades of life, and a strong female predilection (male : female, 19 : 50) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after excision is not expected. In the literature, recurrence of two cases of osseous choristoma has been reported [12].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…The most frequent affected site was the posterior dorsal tongue near the circumvallate papillae [ 1 ]. Since their review in 2014, only four additional cases of lingual osseous choristoma were reported, excluding the current case [ 2 – 4 ]. Adhikari et al described two cases occurring on the dorsal tongues of a 15-year-old female and a 21-year-old female [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since their review in 2014, only four additional cases of lingual osseous choristoma were reported, excluding the current case [ 2 – 4 ]. Adhikari et al described two cases occurring on the dorsal tongues of a 15-year-old female and a 21-year-old female [ 2 ]. Davidson et al reported a case occurring on the tongue base in an 11-year-old male [ 3 ].…”
Section: Discussionmentioning
confidence: 99%